Potential of lithium-ion batteries in renewable energy. (April 2015) - Diouf, Boucar; Pode, Ramchandra
Abstract: The potential of lithium ion (Li-ion) batteries to be the major energy storage in off-grid renewable energy is presented. Longer lifespan than other technologies along with higher energy and power densities are the most favorable attributes of Li-ion batteries. The Li-ion can be the battery of first choice for energy storage. Nevertheless, Li-ion batteries to be fully adopted in the renewable energy sector need a price reduction that most likely will be due to the mass production. The progress in Li-ion batteries needs to be carried further to match enough energy and power densities for the electric vehicle. We present the electric vehicle sector as the driving force of Li-ion batteries in renewable energies. We believe that the development of the electric vehicle industry could be the driving force for the renewable sector making Li-ion batteries more affordable as a benefit of mass production. In the development of Li-ion technology, the electric automobile will be accompanied by other sectors such as grid storage, consumer electronics, the electric bike, military or other medical applications. We present the incomparable advantages of Li-ion batteries over other technologies even if some challenges are still to overcome for a wider usage in stationary energy storage. Highlights: Li-ion battery. Development electric automobile. Li-ion batteries in renewable energy. Cost evolution of Li-ion batteries.